DI-085 Adverse reactions to radiopharmaceuticals: literature review of the past 70 years. (24th February 2014) - Rotondo, G; Nardella, G; Rinaldi, M; Modoni, S
Abstract : Background: Till now very few reports on adverse reactions to radiopharmaceuticals (ADR) can be found in the literature. Over a period of 70 years no more than 34 articles have been published. The authors focus on the importance of proper data collection and the necessity of sharing results. Purpose: To investigate how many and which types of ADR are reported in scientific literature. We reviewed articles from 1955 up to today. Materials and methods: The databases of PubMed, Embase, MedLine, Cochrane, Biomed Central, Google Scholar were searched up to September 2013 looking for reports on ADR. Results: Radiopharmaceuticals cause adverse reactions. 12 cases of adverse reactions with radiopharmaceuticals were found: 3 cases with 18 F-fluorodeoxyglucose (FDG), 8 cases with technetium 99m ( 99m Tc), 1 with iodine-131-metaiodobenzyl guanidine ( 131 I-MIBG). Of these, a total of 5 ADR were specifically described as type I hypersensitivity reactions (anaphylactic). Other symptoms reported are: nausea, circulatory collapse, hypotension, pruritus, bronchospasm, wheezing, dermographism and vomiting. 8 cases with false positive reactions were found with FDG. Conclusions: There is a lack of information on ADR. Few studies have been carried out over the past 60 years. More studies are necessary to report as many cases as possible through active pharmacosurveillance. No conflict of interest.